2023
DOI: 10.1021/acs.jpca.2c06878
|View full text |Cite
|
Sign up to set email alerts
|

Soot Formation in Methane Pyrolysis Reactor: Modeling Soot Growth and Particle Characterization

Abstract: Methane pyrolysis is a very attractive and climate-friendly process for hydrogen production and the sequestration of carbon as solid material. The formation of soot particles in methane pyrolysis reactors needs to be understood for technology scale-up calling for appropriate soot growth models. A monodisperse model is coupled with a plug flow reactor model and elementary-step reaction mechanisms to numerically simulate processes in methane pyrolysis reactors, namely, the chemical conversion of methane to hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Neither of the two alcohol fuels, whose main effect was attributed to an influence on the concentrations of small molecular species such as acetylene and propargyl, led to a significant reduction in soot yield . Not only in the context of transportation fuels but also with respect to the pyrolysis of methane as an attractive and climate-friendly process for hydrogen production and carbon sequestration, the reliable prediction of soot particle formation is an important issue, especially for upscaling purposes, as reported by Shirsath et al They simulated the conversion of methane to hydrogen in a pyrolysis reactor, including aromatics growth and soot formation, and combined their numerical study with the characterization of soot sampled from experiments in a high-temperature pyrolysis reactor …”
Section: Fuels and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of the two alcohol fuels, whose main effect was attributed to an influence on the concentrations of small molecular species such as acetylene and propargyl, led to a significant reduction in soot yield . Not only in the context of transportation fuels but also with respect to the pyrolysis of methane as an attractive and climate-friendly process for hydrogen production and carbon sequestration, the reliable prediction of soot particle formation is an important issue, especially for upscaling purposes, as reported by Shirsath et al They simulated the conversion of methane to hydrogen in a pyrolysis reactor, including aromatics growth and soot formation, and combined their numerical study with the characterization of soot sampled from experiments in a high-temperature pyrolysis reactor …”
Section: Fuels and Mechanismsmentioning
confidence: 99%
“…32 Neither of the two alcohol fuels, whose main effect was attributed to an influence on the concentrations of small molecular species such as acetylene and propargyl, led to a significant reduction in soot yield. 32 Not only in the context of transportation fuels but also with respect to the pyrolysis of methane as an attractive and climate-friendly process for hydrogen production and carbon sequestration, the reliable prediction of soot particle formation is an important issue, especially for upscaling purposes, as reported by Shirsath et al 33 They simulated the conversion of methane to hydrogen in a pyrolysis reactor, including aromatics growth and soot formation, and combined their numerical study with the characterization of soot sampled from experiments in a high-temperature pyrolysis reactor. 33 Alternative fuel options include nitrogen-containing molecules, the use of which, however, may lead to concerns about nitrogen oxide (NO x ) and other emissions.…”
Section: ■ Molecules and Reactionsmentioning
confidence: 99%
“…The thermal decomposition of methane is considered a moderately endothermic reaction. Non-catalytic methane thermal decomposition reactions generally require hightemperature conditions given the strength of the C-H bonds [30,35,[42][43][44][45][46][47][48]. Methane begins to decompose and produce a small percentage of hydrogen at temperatures at or above approximately 1000-1100 • C [30,35,[45][46][47][48].…”
Section: Determining Basic Model Configurationmentioning
confidence: 99%
“…Methane begins to decompose and produce a small percentage of hydrogen at temperatures at or above approximately 1000-1100 • C [30,35,[45][46][47][48]. Furthermore, it has been suggested that methane is almost entirely decomposed at temperatures at or above approximately 1150 • C, corresponding to a hydrogen yield of approximately 0.85-0.97 [35,[42][43][44]47,48]. Therefore, we conducted heat transfer and reaction analyses to determine the basic configuration of the counterflow double-pipe heat exchanger capable of achieving a target temperature of 1200 • C considering a high-temperature T 2 fluid in the inner pipe and low-temperature fluid T 1 in the outer pipe.…”
Section: Determining Basic Model Configurationmentioning
confidence: 99%
“…The latter can agglomerate to ultimately form elemental carbon in the form of soot and graphite. [18][19][20][21][22] Notably, the operation conditions strongly influence the nature, type, and morphology of the accrued carbon. 23 These carbon properties can be a decisive factor for the economic competitiveness of the pyrolysis process, which relies on a commercial usage of both gaseous hydrogen and solid carbon, e.g.…”
Section: Introductionmentioning
confidence: 99%